THE ISSUE OF LEGITIMACY OF THE LATVIAN POLITICAL SYSTEM - Ozolzīle, Gunārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
A democratic political system can be sustainable and stable only if it has society’s support that is based on legitimacy. So far, the attention of Latvian researchers has mostly been devoted to the so-called “ratings” of separate political institutions and politicians, but no attempt has been undertaken to investigate the political system as a whole through the prism of legitimacy. The aim of the present article is to explore whether there is a sufficient resource of legitimacy of the Latvian political system in order to provide stability and efficiency of the regime. The empirical basis of the research mostly consists of the results of the sociological research conducted in Latvia during the past six years (2011–2016). The data analysis of the present research is based on David Easton and Pippa Norris’ conceptual approach to the study of legitimacy of political systems. One of the conclusions that can be made is that the political system of Latvia is characterised by insufficient diffuse support, which then indicates that the political system experiences the problem of legitimacy. As there is a divided society in Latvia, both communities lack a shared national identity, which could connect the society. In addition, it can be stated that around half of the society is not satisfied with the functioning of the political regime. The analysis performed in the article allows concluding that the trust in political institutions is extremely low and the assessment of the political authority performance is highly negative.